2020
DOI: 10.11648/j.ajaf.20200804.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Manure and Potting Media on Germination and Early Growth of <i>Eucalyptus torelliana</i> F. Muell

Abstract: A field experiment was carried out to determine the growth response of Eucalyptus torelliana F. Muell. to organic manure and potting media. The experiment was conducted within the Nursery site of the Department of Forestry and Wildlife Management Nasarawa State University Lafia. Sampled seedlings were systematically numbered and tagged for easy identification and enumeration, the experiment was laid out in a 4×2×5 factorial experiment in a randomized completely block design (RCBD). Analysis of variance was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(10 reference statements)
0
0
1
Order By: Relevance
“…This study is not in line with the report of Rotowa, and Adeagbo, who recorded a significant effect on the vegetative growth of Gmelina arborea seedlings due to the application of organic fertilizer [30]. Rotowa O. J. et al, [31] in a study carried out on Eucalyptus torelliana asserted that poultry manure positively increases plant height more than other sources of manure. It was earlier reported that nitrogenous fertilizers influenced tree growth of tree seedlings, especially tree height, which could favour vegetative growth [32][33][34][35].…”
Section: Discussioncontrasting
confidence: 81%
“…This study is not in line with the report of Rotowa, and Adeagbo, who recorded a significant effect on the vegetative growth of Gmelina arborea seedlings due to the application of organic fertilizer [30]. Rotowa O. J. et al, [31] in a study carried out on Eucalyptus torelliana asserted that poultry manure positively increases plant height more than other sources of manure. It was earlier reported that nitrogenous fertilizers influenced tree growth of tree seedlings, especially tree height, which could favour vegetative growth [32][33][34][35].…”
Section: Discussioncontrasting
confidence: 81%